Secondary battery and electric device

By optimizing the combination of positive electrode active materials, negative electrode active materials, separator and electrolyte in secondary batteries, the structural stability and cycle performance of secondary batteries under high voltage are solved, achieving higher cycle stability and safety.

CN119340452APending Publication Date: 2025-01-21SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411533856.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing secondary batteries suffer from problems such as positive electrode phase transition, cracking, oxygen release, and electrolyte side reactions under high voltage, which affect cycle performance and safety.

Method used

By controlling the type and content of doping elements in the positive electrode active material, the specific surface area of ​​the negative electrode active material, the areal density of the separator, and the silicon-containing additives in the electrolyte, a specific relationship of 0.000245≤(C*W1*W2)/(S*P)≤1.5625 is satisfied, thereby optimizing the positive electrode structure, promoting Li+ migration, suppressing lattice oxygen release, reducing side reactions at the electrode-electrolyte interface, and forming a uniform and dense interface film.

Benefits of technology

It improves the cycle stability and safety performance of secondary batteries, reduces impedance, enhances the structural stability of the positive electrode, reduces gas production, and improves charge and discharge performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005113779380000021
    Figure BDA0005113779380000021
  • Figure BDA0005113779380000051
    Figure BDA0005113779380000051
  • Figure BDA0005113779380000141
    Figure BDA0005113779380000141
Patent Text Reader

Abstract

The invention discloses a secondary battery and a power utilization device, and belongs to the technical field of batteries, the following relation is met by controlling the content type and content of doped elements of a positive electrode active material, the specific surface area of a negative electrode active material, the surface density of a diaphragm and a silicon-containing additive of an electrolyte: (C * W1 * W2) / (S * P) is more than or equal to 0.000245 and less than or equal to 1.5625, the corrosion of hydrofluoric acid to the positive electrode material can be effectively reduced, the structural stability of the positive electrode material is improved, Li < + > migration is promoted, irreversible release of lattice oxygen is inhibited, side reaction of an electrode-electrolyte interface is reduced, and the structural stability of the pole piece is further improved. Meanwhile, the specific surface area of the negative electrode active material is controlled, more lithium ion diffusion channels are provided, diffusion paths of lithium ions are reduced, formation of a uniform and compact interface film on the negative electrode is promoted, gas production of the secondary battery is reduced, impedance is reduced, and the cycle performance is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a secondary battery and an electrical device. Background Art

[0002] In order to achieve sustainable development of mankind, finding a green, economical and renewable new energy system has become a key task in the 21st century. Secondary batteries, as an important new energy source, have entered thousands of households. With the development of secondary batteries, people have put forward higher requirements for secondary batteries, especially power batteries. Long battery life has become an important factor affecting the application of electric vehicles.

[0003] Increasing the battery cut-off voltage is an economical way to improve battery performance, but high voltage also brings some problems, such as positive electrode phase change, cracks, oxygen release and electrolyte side reactions. Therefore, it is urgent to improve the battery cycle performance from the positive electrode and electrolyte design.

[0004] In view of this, this application is filed. Summary of the invention

[0005] The purpose of the present application is to overcome the deficiencies of the prior art and provide a secondary battery and an electrical device, wherein the secondary battery has excellent cycle stability.

[0006] To achieve the above-mentioned object, the first aspect of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material;

[0007] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes La element and Al element;

[0008] The electrolyte includes a first additive;

[0009] The first additive includes a silicon-containing additive;

[0010] The secondary battery satisfies: 0.000245≤(C*W1*W2) / (S*P)≤1.5625;

[0011] Wherein, C% is the mass percentage of the silicon-containing additive in the electrolyte;

[0012] W1% is the mass percentage of La element in the positive electrode active material;

[0013] W2% is the mass percentage of Al element in the positive electrode active material;

[0014] S m 2 / g is the specific surface area of ​​the negative electrode active material;

[0015] P g / m 2 is the surface density of the diaphragm.

[0016] As an embodiment of the present application, the secondary battery satisfies: 0.001724≤(C*W1*W2) / (S*P)≤0.9375.

[0017] As an embodiment of the present application, the silicon-containing additive includes at least one of the following compounds:

[0018]

[0019] As an implementation scheme of the present application, at least one of the following (a) to (e) is satisfied:

[0020] (a) 0.1≤C≤5;

[0021] (b) 0.1≤W1≤5;

[0022] (c) 0.1≤W2≤5;

[0023] (d) 1≤S≤1.7;

[0024] (e)8≤P≤12.

[0025] As an implementation scheme of the present application, W1:W2=1:(1-10).

[0026] As an embodiment of the present application, the electrolyte includes a second additive, and the second additive includes at least one of methylene methanedisulfonate, 1,3-propane sultone, and propenyl-1,3-sultone.

[0027] As an embodiment of the present application, the electrolyte further includes a third additive, and the third additive includes at least one of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, and difluoroethylene carbonate.

[0028] As an implementation scheme of the present application, C:P=(0.0004-0.003):1.

[0029] As an embodiment of the present application, the positive electrode active material includes Li a Ni x Co y Mn z M b La c Al (1-x-y-z-b-c) O dAt least one of the compounds shown;

[0030] Among them, 0.9≤a≤1.1, 0<x<1, 0<y<1, 0<z<1, x+y+z<1, 0≤b≤0.1, 0<c<1, 0<1-xyzbc<1, 1≤d≤2;

[0031] M includes at least one of Zr, W, Zn, Cu, Cr, Mg, Fe, V, Y, Nb, Ti, In, Ce, Sr, Sb, and B.

[0032] A first aspect of the present application provides an electrical device, comprising the secondary battery described above.

[0033] The beneficial effect of the present application is that the present application controls the type and content of the doping elements in the positive electrode active material, the specific surface area of ​​the negative electrode active material, the surface density of the diaphragm, and the silicon-containing additive in the electrolyte to satisfy the following relationship: 0.000245≤(C*W1*W2) / (S*P)≤1.5625, which can effectively reduce the corrosion of the positive electrode plate by hydrofluoric acid and improve the structural stability of the positive electrode plate. La and Al elements are added to the positive electrode active material to form La-O and Al-O bonds, which weaken the covalency of the transition metal-oxygen bond (TM-O bond) and promote the localization of oxygen covalent electrons, thereby promoting Li + It migrates and inhibits the irreversible release of lattice oxygen, reduces side reactions at the electrode-electrolyte interface, and controls the specific surface area of ​​the negative electrode active material, provides more lithium ion diffusion channels, reduces the diffusion path of lithium ions, promotes the formation of a uniform and dense interface film at the negative electrode, reduces secondary battery gas production, reduces impedance, and effectively improves cycle performance. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0035] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0036] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0037] The embodiment of the present application provides a secondary battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material;

[0038] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes La element and Al element;

[0039] The electrolyte includes a first additive;

[0040] The first additive includes a silicon-containing additive;

[0041] The secondary battery satisfies: 0.000245≤(C*W1*W2) / (S*P)≤1.5625, for example, 0.000245, 0.0005, 0.001, 0.0015, 0.001724, 0.002, 0.004, 0.005, 0.006, 0.007184, 0.007353, 0.008, 0.008621, 0.009, 0.01, 0.010776, 0.12, 0.0125, 0.13 , 0.14, 0.15, 0.16, 0.17, 0.017241, 0.02, 0.03, 0.034483, 0.04, 0.05, 0.051724, 0.06, 0.068966, 0.07, 0.086207, 0.1, 0.2, 0.3, 0.4, 0.4, 0.6, 0.7, 0.8, 0.9375, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.5625 or a range consisting of any two of them;

[0042] Wherein, C% is the mass percentage of the silicon-containing additive in the electrolyte;

[0043] W1% is the mass percentage of La element in the positive electrode active material;

[0044] W2% is the mass percentage of Al element in the positive electrode active material;

[0045] S m 2 / g is the specific surface area of ​​the negative electrode active material;

[0046] P g / m 2 is the surface density of the diaphragm.

[0047] The inventors of the present application have found that controlling the doping elements of the positive electrode active material, the specific surface area of ​​the negative electrode active material, the surface density of the separator, and the content of silicon-containing additives in the electrolyte of the secondary battery can affect the performance of the secondary battery. The present application controls the type and content of the doping elements of the positive electrode active material, the specific surface area of ​​the negative electrode active material, the surface density of the separator, and the silicon-containing additives in the electrolyte to satisfy the following relationship: 0.000245≤(C*W1*W2) / (S*P)≤1.5625, which can effectively reduce the corrosion of the positive electrode material by the hydrofluoric acid produced by the side reaction in the electrolyte, improve the structural stability of the positive electrode material, and add La and Al elements to the positive electrode active material to form La-O and Al-O bonds, which weaken the covalency of the TM-O bond and promote the localization of oxygen covalent electrons, thereby promoting Li + Migrate and inhibit the irreversible release of lattice oxygen, reduce the side reactions at the electrode-electrolyte interface, and further improve the structural stability of the pole piece. At the same time, control the specific surface area of ​​the negative electrode active material, increase the contact area between it and the electrolyte, provide more lithium ion diffusion channels, reduce the diffusion path of lithium ions, promote the formation of a uniform and dense interface film at the negative electrode, reduce the gas production of the secondary battery, and improve the safety performance of the secondary battery. The limitation of the density of the diaphragm film can reduce the impact of external forces such as puncture or extrusion on the diaphragm, further improve the safety performance of the secondary battery, and take into account the circulation of the electrolyte containing silicon additives in the diaphragm, reduce impedance, improve charge and discharge performance, and effectively improve the cycle performance.

[0048] In one embodiment, the secondary battery satisfies: 0.001724≤(C*W1*W2) / (S*P)≤0.9375, and in particular, controlling the value of (C*W1*W2) / (S*P) within this range can further improve the cycle stability and further reduce the DCR.

[0049] In one embodiment, the secondary battery satisfies: 0.007184≤(C*W1*W2) / (S*P)≤0.086207, and in particular, the value of (C*W1*W2) / (S*P) is controlled within this range, which further improves the cycle stability and further reduces the DCR.

[0050] In one embodiment, the silicon-containing additive (hereinafter referred to as additives A1 to A11) includes at least one of the following compounds:

[0051]

[0052] In one embodiment, 0.1≤C≤5, for example, it can be 0.1, 0.2, 0.4, 0.5, 0.6, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.5, 3, 3.5, 4, 4.5, 5 or a range consisting of any two of the values; due to the introduction of La and Al elements in the positive electrode active material, the formation of La-O and Al-O bonds weakens the covalency of the TM-O bond and promotes the localization of oxygen covalent electrons, thereby promoting Li + Migration and inhibition of irreversible release of lattice oxygen reduce the side reaction of the electrode-electrolyte interface. By controlling the amount of the silicon-containing additive within this range, the corrosion of the positive electrode material by the hydrofluoric acid produced by the side reaction in the electrolyte can be further reduced, the formation of a stable and dense interface film can be promoted, the reversibility of lithium ions in the process of lithium insertion and extraction of the positive electrode material can be improved, the structural stability of the positive electrode material can be improved, the interface impedance can be reduced, and the structural stability of the pole piece can be further improved, thereby improving the cycle performance of the secondary battery.

[0053] In one embodiment, 0.1≤C≤2, for example, it can be 0.1, 0.2, 0.4, 0.5, 0.6, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.5, 3 or a range consisting of any two of these values. In particular, when the amount of the silicon-containing additive is within this range, the structural stability of the positive electrode sheet can be more effectively improved, and a denser and more stable interface film can be formed.

[0054] In one embodiment, 0.1≤W1≤5, for example, it can be 0.1, 0.2, 0.4, 0.5, 0.6, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.5, 3, 3.5, 4, 4.5, 5 or a range consisting of any two of the values. By controlling the doping amount of the La element within this range, the La-O bond can be more effectively formed, and the La-O bond formed by the Al element doping can cooperate with the Al-O bond to weaken the covalency of the TM-O bond, promote the localization of the oxygen covalent electrons, and thus promote the Li + It migrates and inhibits the irreversible release of lattice oxygen, stabilizes the surface structure of the positive electrode active material, reduces the side reaction between it and the electrolyte, reduces the decomposition rate of the electrolyte, and improves the stability of the electrolyte. In addition, it can prevent the positive electrode active material from pulverizing and falling off during long-term charging and discharging, which helps to maintain the ion permeability of the diaphragm.

[0055] In one embodiment, 0.1≤W1≤4, for example, it can be 0.1, 0.2, 0.4, 0.5, 0.6, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.5, 3, 3.5, 4 or a range consisting of any two of these values. In particular, controlling the doping amount of the La element within this range can more effectively weaken the covalency of the TM-O bond and reduce the side reactions at the electrode-electrolyte interface.

[0056] In one embodiment, 0.1≤W2≤5, for example, it can be 0.1, 0.2, 0.4, 0.5, 0.6, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.5, 3, 3.5, 4, 4.5, 5 or a range consisting of any two of the values. By controlling the doping amount of the Al element within this range, the Al-O bond can be more effectively formed, and the La-O bond formed by the La element doping can be synergistically weakened. The covalency of the TM-O bond is promoted, and the oxygen covalent electron localization is promoted, thereby promoting the Li + It migrates and inhibits the irreversible release of lattice oxygen, which is more conducive to the embedding and extraction of lithium ions, reduces the side reactions at the electrode-electrolyte interface, improves the structural stability, strengthens the grain boundaries between the primary particles of the positive electrode active material, and inhibits the internal stress and breakage of the secondary particles caused by repeated lattice changes during the charge and discharge process. It helps to maintain the integrity of the positive electrode structure, reduce the mechanical stress on the diaphragm, improve the structural stability, and inhibit the dissolution of transition metals in the positive electrode active material during the charge and discharge process (the dissolution of transition metals will lead to an increase in the concentration of metal ions in the electrolyte), thereby reducing the side reactions of the electrolyte.

[0057] In one embodiment, 0.1≤W2≤3, for example, it can be 0.1, 0.2, 0.4, 0.5, 0.6, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.5, 3 or a range consisting of any two of the values. In particular, when the doping amount of the Al element is within this range, it is more conducive to the embedding and extraction of lithium ions, reduces the side reactions at the electrode-electrolyte interface, and improves the structural stability.

[0058] Among them, La and Al elements can be incorporated into the positive electrode active material by doping and / or surface coating. It should be noted that the test method for La and Al elements in this application is: cut the positive electrode sheet into small discs with a diameter of 12 mm, take 20 small discs for ICP testing, and refer to EPA6010D-2018 inductively coupled plasma atomic emission spectrometry.

[0059] In one embodiment, 1≤S≤1.7, for example, it can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 or a range consisting of any two of these values. By controlling the specific surface area of ​​the negative electrode active material within this range, the contact area between the negative electrode active material and the electrolyte is further increased, which can provide more lithium ion migration channels, shorten the lithium ion diffusion path, promote the formation of a uniform and dense SEI film, reduce the gas production of the secondary battery, and improve the cycle performance of the secondary battery.

[0060] Among them, in this application, a specific surface area and pore size distribution meter is used to test the specific surface area of ​​the negative electrode active material, and the test standard is GB / T 19587-2017 gas adsorption BET method.

[0061] It should be noted that the present application can obtain negative electrode active materials with different specific surface areas by selecting negative electrode active materials of different brands and different production batches or treating the negative electrode active materials according to existing methods for changing the specific surface area of ​​materials. It should be noted that the above-mentioned methods for changing the specific surface area of ​​materials include but are not limited to grinding method, template method or heat treatment method.

[0062] Exemplarily, the grinding method is to grind the negative electrode active material to change the specific surface area of ​​the negative electrode active material.

[0063] For example, the template method utilizes the characteristics of the template agent to form a pore structure on the surface or inside the negative electrode active material. For example, polystyrene microspheres are used as template agents, and after the material is coated on the surface of the negative electrode active material, the polystyrene microspheres are removed by pyrolysis or dissolution, thereby changing the specific surface area of ​​the negative electrode active material.

[0064] Illustratively, the heat treatment method is to heat-treat the negative electrode active material, thereby changing the specific surface area of ​​the negative electrode active material.

[0065] In one embodiment, 8≤P≤12, for example, it can be 8, 9, 10, 11, 12 or a range consisting of any two of these values. By controlling the surface density of the diaphragm within this range, the mechanical strength of the diaphragm can be effectively improved, the impact of external forces such as puncture or extrusion on the diaphragm can be reduced, the resistance of lithium ions passing through the diaphragm can be reduced, the migration rate of lithium ions can be increased, and the internal resistance of the secondary battery can be improved, the charging and discharging efficiency can be improved, and sufficient pathways can be provided to promote the formation of a uniform and dense SEI film, thereby improving the cycle performance of the secondary battery.

[0066] The test method for the surface density of the diaphragm is as follows: stack the diaphragm in 5 to 10 sheets, press tightly, and remove the air in the diaphragm. Cut the samples according to the cutting board to obtain several samples, measure the length and width of each sample, calculate the area of ​​each sample, and then weigh each sample separately. Finally, calculate the surface density of each sample according to the formula "surface density = weight / area", and then take the average value as the final surface density.

[0067] In one embodiment, W1:W2=1:(1-10), for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or a range consisting of any two of these values. Controlling the value of W1:W2 within this range can promote the formation of a uniform and dense interface film at the negative electrode, reduce impedance, enhance the ion conductivity of the SEI film, and effectively improve the cycle performance.

[0068] In one embodiment, the electrolyte includes a second additive, and the second additive includes at least one of methylene methane disulfonate, 1,3-propane sultone, and propenyl-1,3-sultone.

[0069] In one embodiment, the electrolyte further includes a third additive, and the third additive includes at least one of vinylene carbonate, vinyl carbonate, fluoroethylene carbonate and difluoroethylene carbonate.

[0070] In one embodiment, C:P = (0.0004-0.003): 1, for example, it can be 0.0004:1, 0.0005:1, 0.0006:1, 0.0007:1, 0.0008:1, 0.0009:1, 0.001:1, 0.002:1, 0.003:1 or a range consisting of any two of these values. Controlling the value of C:P within this range can promote the formation of a more stable and dense interface film, provide a more sufficient path for the circulation of the electrolyte, and at the same time improve the stability of the electrode, thereby effectively improving the cycle stability and reducing the impedance.

[0071] In one embodiment, the positive electrode active material includes Li a Ni x Co y Mn z M b La c Al (1-x-y-z-b-c) O d At least one of the compounds shown;

[0072] Among them, 0.9≤a≤1.1, 0<x<1, 0<y<1, 0<z<1, x+y+z<1, 0≤b≤0.1, 0<c<1, 0<1-xyzbc<1, 1≤d≤2;

[0073] M includes at least one of Zr, W, Zn, Cu, Cr, Mg, Fe, V, Y, Nb, Ti, In, Ce, Sr, Sb, and B.

[0074] In one embodiment, the electrolyte further includes a lithium salt, and the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium difluorobis(oxalatophosphate) (LiDFOP), lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).

[0075] In one embodiment, the mass percentage of the lithium salt in the electrolyte is 8-20%, for example, it can be 8%, 9%, 10%, 11%, 12%, 15%, 16%, 18%, 20% or a range consisting of any two values ​​therein.

[0076] In one embodiment, the electrolyte further includes an organic solvent, and the organic solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), trifluoroethyl carbonate (FEMC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate (MPC), diphenyl carbonate (DPhC), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), ethyl 2,2-difluoroacetate (EDFA), methyl 2,2-difluoroacetate (MDFA), methyl 2,3,3,3-tetrafluoropropionate (M4FP), γ-butyrolactone (γ-GBL), acetonitrile (AN), and sulfolane (TMS).

[0077] In one embodiment, the organic solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), ethyl acetate (EA), methyl propionate (MP), ethyl propionate (EP), and propyl propionate (PP).

[0078] In one embodiment, the negative electrode active material can be graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithium titanate Li4Ti5O 12 , at least one of Li-Al alloy and metallic lithium.

[0079] In one embodiment, the negative electrode active material includes graphite.

[0080] In the present application, there is no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.

[0081] In one embodiment, the negative electrode active material layer further includes a conductive agent and a binder.

[0082] The embodiment of the present application provides a secondary battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material; the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material includes La element and Al element;

[0083] The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes Li a Ni x Co y Mn z M b La c Al (1-x-y-z-b-c) O d At least one of the compounds shown;

[0084] Among them, 0.9≤a≤1.1, 0<x<1, 0<y<1, 0<z<1, x+y+z<1, 0≤b≤0.1, 0<c<1, 0<1-xyzbc<1, 1≤d≤2;

[0085] M includes at least one of Zr, W, Zn, Cu, Cr, Mg, Fe, V, Y, Nb, Ti, In, Ce, Sr, Sb, and B;

[0086] The electrolyte includes a first additive;

[0087] The first additive includes a silicon-containing additive;

[0088] The secondary battery satisfies: 0.000245≤(C*W1*W2) / (S*P)≤1.5625;

[0089] Wherein, C is the mass percentage of the silicon-containing additive in the electrolyte;

[0090] W1 is the mass percentage of La element in the positive electrode active material;

[0091] W2 is the mass percentage of Al element in the positive electrode active material;

[0092] S m 2 / g is the specific surface area of ​​the negative electrode active material;

[0093] P g / m 2 is the surface density of the diaphragm.

[0094] When the above relationship is satisfied, the positive electrode active material contains Li a Ni x Co y Mn z M b La c Al (1-x-y-z-b-c) O d At least one of the compounds shown and the electrolyte containing silicon additives can further reduce the corrosion of hydrofluoric acid on the positive electrode plate, improve the structural stability of the positive electrode plate, further reduce the side reactions at the electrode-electrolyte interface, provide more lithium ion diffusion channels, reduce the diffusion path of lithium elements, promote the formation of a uniform and dense interface film at the negative electrode, reduce the gas production of the secondary battery, reduce impedance, and further improve the cycle performance.

[0095] In one embodiment, the type of the positive electrode current collector is not particularly limited, and it can be any known material suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper.

[0096] There is no particular restriction on the form of the positive electrode current collector. When the positive electrode current collector is a metal material, the positive electrode current collector may be in the form of metal foil, metal cylinder, metal strip roll, metal plate, metal foil, metal plate mesh, stamped metal, foamed metal, etc. When the positive electrode current collector is a carbon material, the positive electrode current collector may include but is not limited to a carbon plate, a carbon film, a carbon cylinder, etc.

[0097] In one embodiment, the positive electrode active material layer further includes a conductive agent and a binder.

[0098] In one embodiment, the type of the conductive agent mentioned in the present application is not limited, and any known conductive agent can be used.

[0099] In one embodiment, the conductive agent includes at least one of carbon materials such as acetylene black, needle coke, carbon nanotubes, and graphene.

[0100] In one embodiment, the type of the binder mentioned in the present application is not limited, and any known positive electrode binder can be used.

[0101] In one embodiment, the binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, and ethylene-propylene rubber.

[0102] In one embodiment, the separator includes a porous sheet or non-woven fabric having excellent liquid retention properties, including but not limited to polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, and the like.

[0103] In one embodiment, the polyolefin is polyethylene or polypropylene. The above-mentioned materials of the diaphragm can be used alone or in any combination.

[0104] In one embodiment, the separator comprises a polyolefin membrane.

[0105] In one embodiment, the diaphragm includes a polyolefin membrane and a ceramic layer disposed on at least one surface of the polyolefin membrane, wherein the ceramic includes at least one of aluminum oxide, silicon dioxide, boehmite, barium sulfate, aluminum hydroxide, magnesium hydroxide, yttrium-doped zirconium oxide, zirconium oxide, and aluminum hydroxide.

[0106] In one embodiment, the surface density of the diaphragm is changed by adjusting the coating process or parameters, such as unwinding and winding diameters, effective roller surface width and maximum coating width, coating method and speed, coating thickness and accuracy, correction accuracy, and drying temperature.

[0107] In one embodiment, the surface density of the diaphragm is changed by adjusting the coating method; the coating method includes: micro-concave roller coating, scraper coating, spin coating, slit coating, spray coating, dip coating and other conventional methods in the art. It should be noted that the present application is not limited to the coating method, as long as the surface density of the diaphragm can be changed.

[0108] In one embodiment, the secondary battery may include an outer package, which can be used to encapsulate the electrode assembly and the electrolyte.

[0109] In one embodiment, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0110] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.

[0111] An embodiment of the present application provides an electrical device, comprising the secondary battery described above.

[0112] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0113] The present application is further described below with specific embodiments:

[0114] Example 1

[0115] A method for preparing a secondary battery comprises the following steps:

[0116] (1) Preparation of electrolyte: EC and EMC were mixed at a mass ratio of 3:7 in a glove box filled with argon (H2O < 1 ppm, O2 < 1 ppm) at room temperature. The molecular sieve is used to remove water to obtain a mixed solvent, and lithium salt (1M LiPF6) is added gradually to the obtained mixed solvent, and the mixture is stirred continuously and cooled with dry ice to ensure that the temperature of the electrolyte does not rise by more than 2°C, and finally a colorless transparent liquid is obtained, and then vinylene carbonate and additive A1 (TMSP) are added to obtain an electrolyte, wherein the mass percentage of vinylene carbonate is 1%, and the content of TMSP is 0.5%;

[0117] (2) Preparation of positive electrode sheet: The positive electrode active material Li (Ni 0.6 Mn 0.3 Co 0.1)O2(NMC631) is mixed with La(NO3)3.6H2O and Al(OH)3 in ethanol in a stoichiometric ratio, and the mass percentage ratio of La and Al in the positive electrode active material is controlled to be 0.5%; the mixed solution is evaporated at 75°C, and the obtained mixed precursor powder is sintered at 500°C for 5 hours, and then the temperature is increased to 880°C and calcined for 15 hours to obtain a modified positive electrode active material LNCMLAO; then the conductive agent acetylene black (SuperP) and the binder polyvinylidene fluoride (PVDF) are mixed uniformly at a mass ratio of LNCMLAO:SuperP:PVDF=94:3:3, and are uniformly dispersed in 1-methyl-2-pyrrolidone (NMP) to form a uniform black slurry, and the mixed black slurry is coated on both sides of the aluminum foil, and then baked, rolled and cut into pieces to obtain the positive electrode sheet.

[0118] (3) Preparation of negative electrode sheet: The negative electrode active material graphite, the conductive agent acetylene black (SuperP) and the binder SBR are mixed evenly in a mass ratio of graphite:SuperP:SBR=94:3:3, and evenly dispersed in deionized water to form a uniform black slurry. The mixed slurry is coated on both sides of the copper foil, and then baked, rolled and cut into pieces to obtain the negative electrode sheet.

[0119] (4) Preparation of secondary batteries: The prepared positive electrode sheet, separator (7μm PE base film + 3μm boehmite ceramic coating), and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets. The bare battery cell is obtained by winding, hot pressing, and welding the tabs. The bare battery cell is placed in an outer packaging aluminum-plastic film and baked in an oven at 85±10℃ for 24h. The prepared electrolyte is injected into the dried battery, allowed to stand, formed, and divided to complete the preparation of the secondary battery.

[0120] Among them, the specific parameters are shown in Table 1, and Y in Table 1 represents the value of (C*W1*W2) / (S*P).

[0121] Embodiments 2 to 5

[0122] The difference between Examples 2 to 5 and Example 1 is that the value of C is adjusted by changing the amount of silicon-containing additive added.

[0123] Embodiment 6-7

[0124] The difference between Examples 6 and 7 and Example 1 is that the value of P is adjusted by changing the surface density of the separator.

[0125] Embodiments 8 to 12

[0126] The difference between Examples 8 to 12 and Example 1 is that the value of W1 is adjusted by changing the amount of La(NO3)3.6H2O added.

[0127] Example 13

[0128] The difference between Example 13 and Example 1 is that the values ​​of W1 and W2 are adjusted by changing the added amounts of La(NO3)3.6H2O and Al(OH)3.

[0129] Embodiments 14 to 18

[0130] The difference between Examples 14 to 18 and Example 1 is that the value of W2 is adjusted by changing the amount of Al(OH)3 added.

[0131] Embodiments 19 to 20

[0132] Compared with Example 3, Examples 19 to 20 change the specific surface area of ​​the negative electrode active material, thereby adjusting the value of S.

[0133] Embodiment 21

[0134] The difference between Example 21 and Example 1 is that the values ​​of C, W1, S, and P are adjusted by adjusting the amount of La(NO3)3.6H2O added, the amount of silicon-containing additives added, the specific surface area of ​​the negative electrode active material, and the surface density of the diaphragm.

[0135] Embodiment 22

[0136] The difference between Example 22 and Example 1 is that the values ​​of C, W1, S, and P are adjusted by adjusting the amount of Al(OH)3 added, the amount of silicon-containing additives added, the specific surface area of ​​the negative electrode active material, and the surface density of the separator.

[0137] Examples 23-24, Comparative Example 5

[0138] The difference between Examples 23 to 24 and Comparative Example 5 and Example 1 is that the values ​​of W1, W2, S, and P are adjusted by adjusting the amount of La(NO3)3.6H2O added, the amount of Al(OH)3 added, the specific surface area of ​​the negative electrode active material, and the surface density of the diaphragm.

[0139] Examples 25 to 27

[0140] The difference between Example 25 and Example 1 is that Example 25 uses an equal amount of Additive A2 to replace Additive A1.

[0141] The difference between Example 26 and Example 1 is that Example 26 uses an equal amount of Additive A3 to replace Additive A1.

[0142] The difference between Example 27 and Example 1 is that Example 27 uses an equal amount of Additive A4 to replace Additive A1.

[0143] Comparative Examples 1 to 3

[0144] The difference between Comparative Examples 1 to 3 and Example 1 is that the values ​​of C, W1, W2, S, and P are adjusted by adjusting the amount of silicon-containing additives, the amount of Al(OH)3, the amount of La(NO3)3.6H2O, the specific surface area of ​​the negative electrode active material, and the surface density of the diaphragm.

[0145] Performance Testing

[0146] 1.DCR growth rate: At 25±2℃, the soft-pack batteries obtained from each implementation case and comparative example were charged to 4.5V at 1C, then discharged at 1C capacity for 30min, adjusted to 50% SOC, and then discharged at 10C constant current pulse for 10s. Then, the SOC was adjusted to 50% according to the above SOC adjustment method, and then charged for 10s. DCR was calculated as (voltage before pulse discharge - voltage after pulse discharge) / discharge current * 100%. After 500 cycles, DCR was tested again, and the DCR change rate = (DCR of 500 cycles - initial DCR) / initial DCR * 100%. The recorded results are shown in Table 1.

[0147] 2. Cycle retention rate: At 25±2°C, the soft-pack batteries obtained from each implementation case and comparative example were subjected to charge and discharge cycle tests at a charge and discharge rate of 1C / 2C in the range of 2.8 to 4.5V, and the battery's first-week discharge capacity and the discharge capacity after 500 cycles were recorded. 500-week capacity retention rate = 500-week discharge capacity / first-week discharge capacity*100%, and the recorded data are shown in Table 1.

[0148] Table 1

[0149]

[0150]

[0151] As can be seen from Table 1, the present application effectively improves the cycle stability and reduces the DCR by controlling 0.000245≤(C*W1*W2) / (S*P)≤1.5625.

[0152] By comparing Examples 1 to 20, 22 with Examples 21, 23, and 24, it can be seen that the present application further improves the cycle stability and further reduces the DCR by controlling 0.001724≤(C*W1*W2) / (S*P)≤0.9375.

[0153] Comparing Examples 1, 3-7, 9-13, 15-20 with Examples 22, 2, 8, and 14, the present application further improves the cycle stability and further reduces the DCR by controlling 0.007184≤(C*W1*W2) / (S*P)≤0.086207.

[0154] By comparing Examples 1, 9 to 12, and 14 with Examples 8, 13, and 15 to 17, it can be seen that the present application further improves the cycle stability and further reduces the DCR by controlling W1:W2=1:(1 to 10).

[0155] By comparing Examples 1, 3, 4, 6, and 7 with Examples 2 and 5, it can be seen that the present application further improves the cycle stability and further reduces the DCR by controlling C:P=(0.0004-0.003):1.

[0156] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, characterized in that: The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material; The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes La element and Al element; The electrolyte includes a first additive; The first additive includes a silicon-containing additive; The secondary battery satisfies: 0.000245≤(C*W1*W2) / (S*P)≤1.5625; Wherein, C% is the mass percentage of the silicon-containing additive in the electrolyte; W1% is the mass percentage of La element in the positive electrode active material; W2% is the mass percentage of Al element in the positive electrode active material; Sm 2 / g is the specific surface area of ​​the negative electrode active material; P g / m 2 is the surface density of the diaphragm.

2. The secondary battery according to claim 1, characterized in that: The secondary battery satisfies: 0.001724≤(C*W1*W2) / (S*P)≤0.9375.

3. The secondary battery according to claim 1, characterized in that: The silicon-containing additive comprises at least one of the following compounds:

4. The secondary battery according to claim 1, characterized in that: Satisfy at least one of the following (a) to (e): (a) 0.1≤C≤5; (b) 0.1≤W1≤5; (c) 0.1≤W2≤5; (d) 1≤S≤1.7; (e)8≤P≤12.

5. The secondary battery according to claim 1, characterized in that: W1:W2=1:(1~10).

6. The secondary battery according to claim 1, characterized in that: The electrolyte includes a second additive, and the second additive includes at least one of methylene methanedisulfonate, 1,3-propane sultone, and propenyl-1,3-sultone.

7. The secondary battery according to claim 1, characterized in that: The electrolyte further includes a third additive, and the third additive includes at least one of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, and difluoroethylene carbonate.

8. The secondary battery according to claim 1, characterized in that: C: P=(0.0004~0.003):

1.

9. The secondary battery according to claim 1, characterized in that: The positive electrode active material includes Li a Ni x Co y Mn z M b La c Al (1-x-y-z-b-c) O d At least one of the compounds shown; Among them, 0.9≤a≤1.1, 0<x<1, 0<y<1, 0<z<1, x+y+z<1, 0≤b≤0.1, 0<c<1, 0<1-xyzbc<1, 1≤d≤2; M includes at least one of Zr, W, Zn, Cu, Cr, Mg, Fe, V, Y, Nb, Ti, In, Ce, Sr, Sb, and B.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Negative active material, negative pole piece, lithium ion battery and electric equipment

    CN115000386A

  • Positive pole piece, secondary battery and electric device

    CN115663118A

  • Lithium battery diaphragm, preparation method thereof and lithium ion battery

    CN117728107A

  • Electrolyte, secondary battery and electric device

    CN118367213A

  • Secondary battery and electric device

    CN118841518A

Cited By

  • Secondary battery and electric device

    CN120376720A